Acceptance of the Punctuality Cascading Reporting System (PCRS) among staffs at National Audit Department in Melaka / Rahayu Abdullah and Nina Nabiha Hassan - Abdullah, Rahayu; Hassan, Nina Nabiha (Faculty of Business and Management, 2016)
The purpose of this research is to find the factors that influence on acceptance of the Punctuality Cascading Reporting System (PCRS) among staffs at National Audit Department. The factors are trust, perceived ease of use, social influence and perceived of usefulness. National Audit Department in Melaka is the first federal institution that uses this system. It also is the first branch of National Audit Department for the trial period using it before implement to other branches in Malaysia. In order to get the result for this research, the researchers have used the software of Statistical Package for the Social Sciences (SPSS) version 22.0 to analyse the data. The information that gathers and findings will be used to know the most factors that influenced to the dependent variable and to improve on acceptance for this system among their staffs.